The Seven-arm Octopus, Haliphron atlanticus Streenstrup, 1861 (Cephalopoda, Alloposidae), in the Fernando de Noronha archipelago, Brazil - Françoise Lima; Liana Mendes; Leonardo Veras; Tatiana Leite; Sergio Lima (Check List, 2017)
The rare deep-sea octopus, Haliphron atlanticus is the only known species recognized within the genus. A fragment of H. atlanticus was found in the Fernando de Noronha archipelago, Brazil (South Atlantic). Both phylogenetic reconstruction and pairwise genetic divergence show that the specimen recorded in South Atlantic is closely related to individuals from North Pacific. However, there is a greater divergence among these specimens and a giant octopus from North Atlantic. This evidence suggests that Haliphron is not monospecific, with at least two species, both represented in the Atlantic Ocean.